Review Artikel: Pengaruh Diet Semangka Merah (Citrullus lanatus) terhadap VO2Max - Annisa Hanifwati; Ajeng Salsabilla Pawestri; Hanna Cakrawati; Anung Putri Illahika (ARTERI : Jurnal Ilmu Kesehatan, 2022)
Technological rapidly developments influence in lifestyle changes of people who do sedentary lifestyles. Lack of physical activity can reduce the value of VO2max, so that will impact on lowering physical fitness index. Value of VO2max can be increased through consumption of red watermelon (Citrullus lanatus) that is contained citrulline. Red watermelon is the richest source of citrulline compared to other fruits or vegetable on cucurbitaceae plants. Substance of citrulline that enters the body is converted to nitric oxide (NO) which can increase VO2max through the mechanism of oxidative phosphorylation in mitochondria. This study is to know the effect of red watermelon (Citrullus lanatus) to VO2max. This paper is a qualitative study of literature. Bibliography like articles and literature books were obtained through the Elsevier, PubMed, Cochrane Library, and Google Scholar search engines. The result of analysis shows that the consumption of red watermelon (Citrullus lanatus) affects of VO2max enhancement. Nutrients of citrulline, which is contained in red watermelon, increases NO bioavailability and has an effect on increasing VO2max. In conclusion consumption of red watermelon juice (Citrullus lanatus) affects to value of VO2max.